Divided Opinion on The Fair Minimum Wage Act of 2013: Random or Systematic Differences - Donal O'Neill (Institute for the Study of Labor (IZA), 2014)
This paper analyses economists' support for the Fair Minimum Wage Act of 2013, by examining the characteristics of almost 1000 economists who signed open letters either supporting or opposing the Bill prior to a Senate debate on the legislation. In contrast to previous work, which found that economists' disagreements were surprisingly random, I find systematic differences between those economists supporting the legislation and those opposing it. There is evidence of a saltwater-freshwater divide in attitudes, with support for the Bill stronger for economists located further from Chicago. In addition support for the legislation is higher among females and those who obtained their PhD outside the US. Financial economists are more likely to oppose the Bill, while those specialising in labour economics are more likely to support it. Furthermore the support among labour economists is strongest for academics who have received their PhD in recent years. This may reflect the impact of recent work in labour economics challenging the traditional competitive model of labour markets.
Keywords: J38; A23; 330; minimum wage; schools of thought